“Tsar and God” - Uspensky, Boris; Zhivov, Victor (Academic Studies Press, 2021)
Featuring a number of distinguished essays by internationally known Russian cultural historians Boris Uspenskij and Victor Zhivov, this collection encompasses various ground-breaking works appearing in English for the first time. Focusing on several of the most interesting and problematic aspects of Russia’s cultural development, these essays examine the survival and reconceptualization of Russia’s past in later systems, and some of the key transformations of Russian cultural consciousness. This volume contains important examples of cultural semiotics and indispensable contributions to the history of Russian civilization.